2005
DOI: 10.2174/156801405774330349
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antihistamines in the Management of Allergic Rhinitis

Abstract: Allergic rhinitis is a common disease worldwide and antihistamines remain the mainstay of pharmacotherapy for allergic rhinitis. Histamine is one of main mediators involved in the disease pathophysiology. The primary mechanism of antihistamine action is believed to be competitive antagonism of histamine receptors, specifically the H 1 -receptors. These receptors are present on nerve endings, smooth muscles, and glandular cells. However, H 1 -antagonism may not be their sole mechanism of action. Antihistamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…There are four general principles for management of allergy: An optimum pharmacological agent for the treatment of AR meets the following criteria: proven safety and efficacy, an easy route of administration with rapid absorption, rapid onset of action with no side effects and, strong antiallergic activity [11,12]. There are four general principles for management of allergy: An optimum pharmacological agent for the treatment of AR meets the following criteria: proven safety and efficacy, an easy route of administration with rapid absorption, rapid onset of action with no side effects and, strong antiallergic activity [11,12].…”
Section: Treatment Strategymentioning
confidence: 99%
See 4 more Smart Citations
“…There are four general principles for management of allergy: An optimum pharmacological agent for the treatment of AR meets the following criteria: proven safety and efficacy, an easy route of administration with rapid absorption, rapid onset of action with no side effects and, strong antiallergic activity [11,12]. There are four general principles for management of allergy: An optimum pharmacological agent for the treatment of AR meets the following criteria: proven safety and efficacy, an easy route of administration with rapid absorption, rapid onset of action with no side effects and, strong antiallergic activity [11,12].…”
Section: Treatment Strategymentioning
confidence: 99%
“…Dale & Laidlaw first studied the physiological effects of histamine and showed that it induced smooth-muscle contraction and vasodilatation in the early 20th century [11,13]. They showed the mechanism between the effect of histamine and the immediate response to an injected outside protein in previously sensitized animals and suggested that histamine might play a role in this reaction.…”
Section: Antiallergic Effects Of Antihistaminesmentioning
confidence: 99%
See 3 more Smart Citations